일개 대학 경비근로자의 수면의 질과 직무스트레스가 건강관련 삶의 질에 미치는 영향 - 박건우(Gun Woo Park); 고수진(Su-Jin Goh); 김동하(Dong Ha Kim); 김혜림(Hye Lim Kim); 박진관(Jin Kwan Park); 유수영(Soo-Young Yu); 정두영(Du Young Jeong); 천진희(Jin-Hee Chun); 황순영(Soon-Young Hwang); 조성일(Sung-Il Cho) (保健敎育健康增進學會誌, 2015)
Objectives: The purpose of this study was to identify the effects of sleep quality and occupational stress on health-related quality of life among a university's security workers. Methods: 128 security workers voluntarily participated in the study. The survey asked demographic, health related, job related factors, the Korean Occupational Stress Scale Short Form(KOSS-SF), sleep quality questionnaire, and 12-Short Form Health Survey version 2.0(SF-12v2). The data were analyzed by using descriptive analysis, t-test, ANOVA, multiple linear regression, and multiple logistic regression. Results: The interrupted rest time was significantly negatively related to occupational stress. The occupational stress significantly affected sleep quality. The significant variable affecting Physical Component Score(PCS) and Mental Component Score(MCS) was sleep quality and occupational stress, respectively. Conclusions: HRQOL was founded to be affected by occupational stress and sleep disorder among the security workers. Based on this study, we suggest that the management of both occupational stress and sleep quality is crucial to improve the HRQOL.